Pengomposan di Yayasan Gerakan Peduli Lingkungan, Pekayon, Bekasi Selatan, Jawa Barat - Badih Badih; Fetty Dwi Rahmayanti (Composite : Jurnal Ilmu Pertanian, 2022)
ABSTRACT The 3R Waste Management Center is located in the Pondok Pekayon Indah housing complex RW 011 Pekayon Jaya sub district, South Bekasi sub district, which is protected by the Environmental Care Movement Foundation, a foundation that has been composting organic waste since 2003. Composting is a process in which organic matter is decomposed biologically, especially by microbes that use organic matter as an energy source. Making compost is to regulate and control this natural process so that compost can form more quickly. The stages of composting carried out by the Environmental Care Movement Foundation include; Garbage collection, waste sorting or sorting, First Enumeration, Transfer and Addition of EM-4 Activator, Fermentation Stage, Second Enumeration, Screening or Screening, Packaging and Storage. The compost produced by the Environmental Care Movement Foundation has been tested by the Laboratory of the Department of Soil Science and Land Resources, Faculty of Agriculture, IPB since 2015 issued by the Sanitation Service of the Bekasi City Government. This is an added value for compost made by the Environmental Care Movement Foundation, because the results of laboratory tests can convince people who will use or even buy compost made by the Environmental Care Movement Foundation. Thus, the compost fertilizer business opportunity for the community (sociopreneurship) is very wide open because the quality of the compost is guaranteed.